Cytotoxic triterpene diglycosides from the sea cucumber Stichopus horrens. Issue 13 (1st July 2017) - Cuong, Nguyen Xuan; Vien, Le Thi; Hoang, Le; Hanh, Tran Thi Hong; Thao, Do Thi; Thanh, Nguyen Van; Nam, Nguyen Hoai; Thung, Do Cong; Kiem, Phan Van; Minh, Chau Van
Graphical abstract: Abstract: Using various chromatographic separation techniques, eight triterpene diglycosides (1 –8 ), including four new compounds namely stichorrenosides A–D (1 –4 ), were isolated from a methanol extract of the Vietnamese sea cucumber S. horrens . Their structures were elucidated based on spectroscopic analyses, including HR ESI MS, 1D and 2D NMR. Their in vitro cytotoxic activity against five human cancer cell lines, Hep-G2 (hepatoma cancer), KB (epidermoid carcinoma), LNCaP (prostate cancer), MCF7 (breast cancer), and SK-Mel2 (melanoma), was evaluated using SRB methods. Stichorrenoside D (4 ), stichoposide A (5 ), and 3 β - O -[ β -d -xylopyranosyl-(1→2)- β -d -xylopyranosyl]-23 S -acetoxyholost-7-ene (7 ) showed strong cytotoxicity on all five tested cancer cell lines, whereas significant effect was observed for stichorrenoside C (3 ) and stichoposide B (6 ).